Resection of a giant bilateral retrovascular intrathoracic goiter causing severe upper airway obstruction, 2 years after subtotal thyroidectomy: a case report and review of the literature - Tsakiridis, Kosmas; Visouli, Aikaterini N.; Zarogoulidis, Paul; Karapantzos, Elias; Mpakas, Andreas; Machairiotis, Nikolaos; Stylianaki, Aikaterini; Christofis, Christos; Katsikogiannis, Nikolaos; Courcoutsakis, Nicolaos; Zarogoulidis, Konstantinos (Journal of Thoracic Disease, 2012)
The intrathoracic (or substernal) goiter is more often benign; but it can be malignant in 2-22% of patients. There is history of prior thyroid surgery in 10% to more than 30% of patients. Intrathoracic goiters cause adjacent structure compression more frequently than the cervical goiters, due to the limited space of the thoracic cage. Compression of trachea, oesophagus, vascular and neural structures may cause dyspnoea, dysphagia, superior vena cava syndrome, subclavian vein thrombosis, hoarseness, and Horner’s syndrome. There is usually progressive deterioration, but acute exacerbation may occur. The presence of a thoracic goiter (>50% of the mass below the thoracic inlet) is per se an indication for resection. Tracheal compression by (cervical or thoracic) goiter is also an indication for resection; early tracheal decompression is recommended particularly in symptomatic patients. In severe respiratory distress, intubation and semi-urgent operation may be required. With early intervention, most intrathoracic goiters can be removed through a cervical approach, while tracheomalakia is avoided. We hereby present successful and uncomplicated total thyroidectomy, through a median sternotomy, of a benign, gigantic, bilateral, retrovascular, posterior mediastinal, intrathoracic goiter, encircling the trachea, and causing severe respiratory distress in a 63 year old man with history of previous subtotal thyroidectomy.